Association between serum bilirubin levels and carotid atherosclerosis: a systematic review and meta-analysis - Yan, Bao-E; Li, Ying; Zhu, Min-Jie; Wang, Qian-Jun; Xiao, Jing; Zhang, Yan; Zhang, Chun-Yan; Zhou, Jing; Han, Tuo (Frontiers in Endocrinology, 2025)
ObjectiveCarotid atherosclerosis (CAS) is a significant factor contributing to cardiovascular events and poses a major public health concern. There are still many controversies about the association between serum bilirubin and CAS. This study aims to provide a systematic review and meta-analysis to examine the association between serum bilirubin levels and carotid atherosclerosis.MethodsAn electronic literature search was performed using PubMed, Web of Science and Embase up to December 2023. Articles were screened based on predefined inclusion criteria and assessed for risk of bias and quality of evidence utilizing the Newcastle-Ottawa Scale and GRADE tool. Pooled mean differences were calculated using a random effects model. Subgroup and meta-regression analyses were performed to identify potential sources of heterogeneity.ResultsNine studies involving 7,023 participants were included in this meta-analysis. The results indicated that patients with carotid atherosclerosis exhibited lower levels of total bilirubin compared to those without (SMD -3.42, 95% CI [-5.18, -1.67]), with a statistically significant difference (z=-3.819, P<0.001). Moreover, a significant inverse association was found between total bilirubin levels and the risk of carotid atherosclerosis (OR 0.79, 95% CI [0.71, 0.88], P<0.001, I²=78.2%). However, substantial heterogeneity was observed (I²=98.0%, P<0.001). Subgroup and meta-regression analyses indicated that sample size and the severity of carotid atherosclerotic lesions might contribute to the heterogeneity observed across studies. The GRADE assessment was low.ConclusionLower serum bilirubin levels are associated with an increased risk of carotid atherosclerosis. This meta-analysis offers new insights into the development of diagnostic biomarkers and therapeutic targets. Further prospective cohort studies are necessary to validate our conclusions.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42023447199.